1985
DOI: 10.1139/v85-276
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between geometries and energies of identity SN2 transition states: the dominant role of the distortion energy and its origin

Abstract: At the 4-31G computational level, the intrinsic barriers of eight identity SN2 reactions X 3-CH3X XCH3 + X-are less than the energies required to distort CH,X from its ground state geometry to its transition state geometry by a constant 25 kcal/mol. The distortion energy and its C-X stretching and H-C-X bending components can be calculated directly, or, alternatively, estimated from the force constants and bond dissociation energies of CH3X. Regardless of the mode of computation, the distortion energies are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
1
2

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 4 publications
1
45
1
2
Order By: Relevance
“…There is a basis for expecting G to be less for the less substituted alkyl bromides. Mitchell et al (60) have reported that G is proportional to the deformation energy for CH3-X. They were considering SN2 reactions but it appears likely that similar effects would apply to SN1 reactions.…”
Section: Discussionmentioning
confidence: 99%
“…There is a basis for expecting G to be less for the less substituted alkyl bromides. Mitchell et al (60) have reported that G is proportional to the deformation energy for CH3-X. They were considering SN2 reactions but it appears likely that similar effects would apply to SN1 reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Such a correlation exists the exchange reactions of P~S -, HS-, HO-, and NC-, ln because the energy requried to dissociate the TS into three fragments accord with eq. [5], the halide exchange series is predicted to in Table 1. The experimental data set is seen to obey the above Table This i index of the reaction series, the looser the average transition state of the series.…”
mentioning
confidence: 97%
“…1. Large Ix: -ARX gaps and delocalization indices (WR:) will require a greater C-X deformation and will thereby lead to looser transition state geometries (5). Since barriers and transition state geometries behave alike, it follows then that the intrinsic selectivity that derives from plots of barriers AE* vs. (Ix, -Am) may serve as an indicator of transition state geometry.…”
mentioning
confidence: 99%
See 2 more Smart Citations